2003
DOI: 10.1046/j.1365-2567.2003.01728.x
|View full text |Cite
|
Sign up to set email alerts
|

Phage display of human antibodies from a patient suffering from coeliac disease and selection of isotype‐specific scFv against gliadin

Abstract: SUMMARYCoeliac disease (CD), a gastrointestinal illness characterized by intestinal malabsorption, results from gluten intolerance accompanied with immunological responses towards gliadin, an ethanol-soluble protein fraction of wheat and other cereals. The role of gliadin in eliciting immune responses in CD is still partly unclear; however, the occurrence of anti-gliadin in the sera of patients suffering from CD correlates well with clinical symptoms. In this work we report the construction of isotype-speci®c,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Since the majority of libraries are generated using a primer combination targeting the variable gene segment and the junction gene segment [26,27], no actual discrimination in terms of isotype responses is made unless isotype-specific reverse primers are used for repertoire generation. However, there is a clear benefit to the use of isotype-specific repertoires for immune library generation [28,29]. Analyzing this concept from an immunological standpoint: as B-cells are activated, class-switch recombination (CSR) occurs to allow switching of antibody production in an immature Bcell from IgM or IgD to isotypes IgG, IgA or IgE.…”
Section: Isotype-specific Repertoirementioning
confidence: 99%
“…Since the majority of libraries are generated using a primer combination targeting the variable gene segment and the junction gene segment [26,27], no actual discrimination in terms of isotype responses is made unless isotype-specific reverse primers are used for repertoire generation. However, there is a clear benefit to the use of isotype-specific repertoires for immune library generation [28,29]. Analyzing this concept from an immunological standpoint: as B-cells are activated, class-switch recombination (CSR) occurs to allow switching of antibody production in an immature Bcell from IgM or IgD to isotypes IgG, IgA or IgE.…”
Section: Isotype-specific Repertoirementioning
confidence: 99%
“…Rhyner et al [ 114 ] reported the construction of three unique isotype ScFv libraries (IgA, IgG, and IgM) from a celiac patient and a healthy control individual, and they demonstrated that all libraries from the celiac patient, but none from the control donor, were selectively enriched in gliadin-binding phage clones after four rounds of biopanning. This method not only resulted in a suitable approach to obtain high-affinity antibodies against gliadin but also allowed for the isotype-specific characterization of the immune responses occurring in a pathological condition.…”
Section: A New Era: Directed Evolution Of Recombinant Antibodiesmentioning
confidence: 99%
“…A chosen number of identified phage clones were tested for their cells binding properties using phage enzyme-linked immunosorbent assay as described previously [14]. When the cells (SK6, IBRS2, PK15, BHK21, COS7, MARC145) growing in 96-well plates reached 100% confluence, 150 ll methanol with 0.15% H 2 O 2 was added in each well, and then kept at RT for 20 min after removing medium.…”
Section: Cells Binding Propertiesmentioning
confidence: 99%